KERANGKA DASAR DALAM PENGEMBANGAN KURIKULUM 2013 - Azis, Rosmiaty (Inspiratif Pendidikan, 2016)
The basic framework of the goals of 2013 curriculum development is to prepare Indonesian people to have the ability to live as faithful, productive, creative, innovative, and affective individuals and citizens, and able to contribute to the society, nation, state, and world civilization. Some new things in the upcoming curriculum include curriculum-based science and integrated thematic curriculum. Curriculum as an educational design has a central position in the overall learning activity. It is also to determine the progress and outcomes of education. Looking at the important role of curriculum in education and the development of life learners later, the curriculum development cannot be done haphazardly. It should be oriented to the clear objectives that will produce good and perfect outputs.